The Predictive Value of Tagalog Voice Morphology in Filler-Gap Dependency Formation - Pizarro-Guevara, Jed Sam; Wagers, Matthew (Frontiers in Psychology, 2020)
Research has shown that when processing filler-gap dependencies, comprehenders do not wait until they encounter all of the bottom-up information in the input. Instead, they use various types of linguistic information to predictively posit a gap that would allow the dependency to be resolved. They can use syntactic (Traxler and Pickering, 1996), lexical (Trueswell et al., 1994), morphological (Kamide et al., 2003), and prosodic (Nagel et al., 1994) information. Here we examine whether Tagalog comprehenders use the language's voice morphology to guide their incremental interpretations. We hypothesized that voice allows comprehenders to commit to an interpretation upon encountering the verb, since they have information about the event structure at this point in time and by virtue of the voice morphology, the thematic role of the filler. In experiment 1, using an acceptability judgment study, we found that comprehenders differed in how they used the different voices in different filler-gap contexts to detect the licitness of displacements. These differences may have consequences for how voice is used in real-time. In experiments 2 and 3, using the stops-making-sense paradigm (Boland et al., 1990), we found that comprehenders used voice as a cue to actively associate the filler with the gap. However, in experiment 3, the way in which they used voice varied by type and varied across types of filler-gap dependencies. We argue that comprehenders were using construction-specific cue validities when processing filler-gap dependencies. However, they also engaged with other classes of linguistic information, including (but not limited to) information about the structural similarities and the thematic complexity of the dependencies involved, and the relative frequency of the different types of voices in the language. These interactions resulted in processing asymmetries.